Relationship between proactive personality, perceived social support, and career decision making self-efficacy among final-year students in public universities of Selangor - Sivanesan, Nithyalakshmi; Mohd Khir, Azlina (Human Resources Management Academic Research Society (HRMARS), 2024)
Studying career decision-making self-efficacy among final-year students is crucial because it affects students' readiness and confidence in making informed career choices. Understanding factors such as proactive personality traits and perceived social support ultimately leads to improved career outcomes and reduced uncertainty. The study aimed to determine the relationships between proactive personality, perceived social support, and career decision making self-efficacy among final-year students in public universities in Selangor, Malaysia. 359 respondents selected through simple random sampling, participated in the study. Data were collected via self-administered questionnaires using the Proactive Personality Scale, Multidimensional Scale of Perceived Social Support, and Career Decision-Making Self-Efficacy Short Form. Statistical analysis used were the Pearson correlation and multiple regression. Findings revealed that the respondents’ proactive personalities were at a medium level, while perceived social support and career decision-making self-efficacy were at a high level. Moreover, findings indicated positive significant relationships between proactive personality and perceived social support with career decision-making self-efficacy. The multiple regression analysis showed that proactive personality and perceived social support explained 44.6% variances in career decision-making self-efficacy. These findings suggest that enhancing individuals' proactive personality traits and increasing their perceived social support could substantially improve their confidence in making career decisions.